"Resiliency Humanitarianism": Responsibilizing Refugees through Humanitarian Emergency Governance in the Camp1. Issue 4 (20th November 2015) - Ilcan, Suzan; Rygiel, Kim
Abstract : Scholarly interest in the camp has grown over recent years, inspired in part by Giorgio Agamben's (1995; Homo Sacer: Sovereign Power and Bare Life ) work. Scholarship in this area has built on Agamben's view of the camp as an abject space of exception and bare life but also, in reaction to this view, has theorized the camp as a political and social space which constitutes refugees and displaced persons as political subjects, active in demanding rights and social justice. Building on existing scholarship, this article draws attention to another important trend in the camp which has emerged alongside the growing activism of refugee populations, dissatisfied with their lack of rights and abject conditions. This is the trend of engaging refugees to become self‐governing in the management of the camp, to think of the camp in terms of community development, with camp life providing the experiences through which refugees are to refashion themselves as resilient, entrepreneurial subjects. Our analysis examines this trend through the issue of humanitarian emergency governance of refugees and IDPs and within the context of reforms undertaken by the United Nations—specifically, through what we term "resiliency humanitarianism." We use this term to suggest a particular rationale of care, camp coordination, and management which emerges within neoliberal government and which focuses on assisting refugees and IDPs to adapt to, and survive, crisis with the aim of responsibilizing them.